(untitled) (Research, Society and Development, 2024)
This study aims I am analyze the Comparative Governance and Risk Management process in organizations listed on B3’s Novo Mercado, cyclical consumption sector, commercial subsector, miscellaneous products segment. Therefore, this article sought I am analyze the participation of Risk Management mechanisms and External auditing of companies listed on B3 in the period from 2019 to 2022. Regarding methodology, the study can be classified as bibliographic and descriptive research, with a qualitative approach. based on the analysis of reference forms and financial statements of companies listed on B3’s Novo Mercado. For the analysis, the researchers created an instrument as a guide for obtaining the results. The article was divided into three sections, the first is the theoretical foundation with the items of accounting audit and financial statements, corporate governance and stakeholder theory and corporate risk management. The conclusions were reached that the reliability mechanisms for the information provided by companies are fragile I am the point where signs of errors and fraud are made public.